Вдосконалення технологій проведення рефакторингу баз даних для інформаційних систем - Струзік, Владислав Анатолійович (My University, 2020)
Досліджено класифікацію сучасних інформаційних систем та розглянуті два підходи побудови сервісів, а саме: монолітний шаблон архітектури та мікросервісний шаблон архітектури. Описані їх переваги та недоліки, а також наведені рекомендації щодо використання різних варіантів взаємодії з базами даних при розробці відповідно до мікросервісного шаблону архітектури. Наведено основні ознаки необхідності проведення рефакторингу, недоліки та проблеми рефакторингу баз даних. Описано процес рефакторингу баз даних. The classification of modern information systems is investigated and two approaches of building services are considered, namely: monolithic architecture template and microservice architecture template. Their advantages and disadvantages are described, as well as recommendations on the use of different options for interaction with databases in the development of microservice template architecture. This dissertation is based on the analysis of code refactoring and database refactoring. The main features of the need for refactoring, defects and problems of databases refactoring are given. The process of refactoring databases is described directly. The necessity of refactoring is substantiated, the recommendations on the choice of the appropriate refactoring operation and on the implementation of refactoring are given. Accordingly, the description and features of the refactoring categories and their operations are provided. The concept of semantic database versioning is formulated and recommendations are given for its application.
Keywords: інформаційна система; рефакторинг; програмне забезпечення; семантичне версіонування; база даних; архітектурний шаблон; information system; refactoring; software; semantic versioning; architectural template; databases